Modelling South African cold-water coral habitats - De Haast, James Andrew (Department of Biological Sciences, 2020)
Cold-water corals are found globally but little is known about energy flows associated with these habitats. The degree to which the benthic ecosystems containing cold-water corals are linked to the overlying pelagic ecosystems is also poorly understood. Observational studies have indicated that fish abundance is greater in the waters surrounding coldwater coral reefs compared to nearby waters over barren seafloor, implying enhanced productivity in the cold-water coral ecosystems. Support for this hypothesis is tested in this study using a customised Ecopath with Ecosim model. The model is applied to Childs Bank, a region on the west coast of South Africa located in the southern Benguela eastern boundary ecosystem. A previously constructed Ecopath model of the southern Benguela was modified to represent the main groups of organisms found on Childs Bank and additional groups were added to better represent the main groups associated with cold-water coral. In total, including the additional compartments, the model ecosystem consisted of 34 living compartments and three non-living compartments. Three novel living compartments were considered in the model: Cold-water corals, Sponges and Tube-worms. Two additional non-living compartments comprised Coral skeleton and Coral mucus. The Ecopath model was balanced by assuming that the three additional living groups had the same production to biomass ratios as the Macrobenthos group. The production to consumption ratio of Sponges and Cold-water corals were sourced from literature. An unconstrained non-linear minimisation function was used to solve for the biomass of the Sponge and Cold-water coral groups as their production was needed for the Ecopath model to balance; thus a biomass estimate was required for both these groups. The balanced Ecopath model was used in an Ecosim model, which was applied to three scenarios designed to investigate whether trophic links in the cold-water coral ecosystems could account for increased fish abundance: scenario 1, the removal of both cold-water coral and cold-water coral skeleton; scenario 2, changes in fishing pressure on small pelagic fish; scenario 3, the removal of coldwater coral skeleton without damage to the living coral. Scenario 3 is an artificial scenario designed to isolate the effects of cold-water coral skeleton loss from the trophic interactions from the living cold-water corals. None of the scenarios produced results with notable changes in biomasses of groups in the wider ecosystem. It is thus hypothesised that enhanced fish production results from cold-water corals changing the local oceanographic conditions through their physical structure rather than primarily by their trophic interactions.